(untitled) (Ustozlar uchun, 2025)
This article investigates the role of inclusive education practices in modern schools and their effects on learners with diverse abilities and backgrounds. It illustrates how frameworks such as Universal Design for Learning (UDL), differentiated instruction, collaborative teaching, and assistive technologies contribute to equitable access, improved engagement, and academic success for all students. The study also outlines persistent challenges: lack of resources, insufficient teacher training, and social–cultural barriers. The article concludes that implementing comprehensive inclusive practices is essential for fostering equity, social cohesion, and educational quality in contemporary schooling.